Penerapan Asas Primum Remedium terhadap Penipuan dan Penggelapan Dana Koperasi Jenis Simpan Pinjam - Arie Kartika; Rafiqi Rafiqi; Windy Sri Wahyuni (Jurnal Ilmiah Penegakan Hukum, 2022)
This article aims to discuss the application of the Primum Remedium Principle to Fraud and Embezzlement of Savings and Loans Cooperative Funds. The problem is focused on legal arrangements for fraud and embezzlement of savings and loan cooperative funds and the application of the primum remedium principle against fraud and embezzlement of savings and loan cooperative funds. To approach this problem, normative juridical research is used. The data were collected through literature study and analyzed qualitatively. This study concludes that the legal regulation of the criminal act of fraud and embezzlement of Savings and Loans Cooperative funds is not explicitly stated in the provisions of the cooperative regulations, then the Criminal Code (KUHP) is applied where fraud is regulated in Article 378 of the Criminal Code, while embezzlement is regulated in Article 372 KUHP. The Primum Remedium principle against criminal acts of fraud and embezzlement of savings and loan cooperative funds can be applied based on reports, investigations, investigations and losses caused to creditors and threatens to hamper financial system stability. Primum remedium principle as the main means in a statutory provision or prioritizing the implementation of criminal law in cooperatives because of the context of the situation, however, the use of such criminal law facilities must also be considered from the point of view of the greatest benefit, especially to create a healthy national economic system development in a future period. will come